Ecology and diversity of wildlife in Dhaka University Campus, Bangladesh - Shome, Ashikur Rahman; Alam, Md Mahabub; Rabbe, Md Fazle; Rahman, Md Mokhlesur; Jaman, Mohammad Firoj (Dhaka University Journal of Biological Sciences, 2022)
Nowadays urbanization continues, and poses a serious threat to wildlife globally. A survey-based study on wildlife was conducted for three years from March 2017 to February 2020 in Dhaka University campus. Data was collected through direct visual encounter observations. A total of 94 species of wildlife under 20 orders and 52 families were observed. Of the documented wildlife, 5 (5.32%) species belongs to amphibians, 10 (10.64%) reptiles, 70 (74.47%) birds and 9 (9.57%) mammals. The highest species richness (72, 76.60%) was observed in the third year (March 2019 to February 2020), particularly in winter season. Although the lowest richness was (63, 67.02%) found in the first year (March 2017 to February 2018), but the evenness was the highest this year, particularly in summer season. We counted the highest number of individuals (n=5227, 35.73%) in the first year (March 2017 to February 2018) but these counts have gradually decreased with the lowest in the third year (March 2019 to February 2020). Among 94 species, 44 species (46.80%) were very common, 3 (3.19%) common, 17(18.09%) uncommon and 30 (31.91%) were few. Duttaphrynus melanostictus was the most abundant (66.89%) among amphibians, Hemidactylus frenatus (40.82%) for reptiles, Psittacula krameri (18.73%) for birds and Mus musculus (28.68%) for mammals. Rampant human movements and sound pollution were frequent inside the campus that might affect wildlife. Therefore, long-term systematic monitoring is necessary to understand the species diversity and population trend of wildlife in the campus. Moreover, this baseline information may help urban policymakers to take proper management measures for the protection of wildlife in the study area. Dhaka Univ. J. Biol. Sci. 30(3 CSI): 429-442, 2022 (June)